Optimalisasi Dana Desa: Studi Efektivitas Peraturan Keuangan 2025 dalam Perspektif Siyasah Maliyah - Habibi (Bahasa Indonesia, 2026)
This research aims to analyze the effectiveness of the 2025 Financial Regulations in optimizing village fund management and review it from a siyasah maliyah perspective. Using qualitative methods with a juridical-normative approach and field studies in several sample villages, this research found that although the 2025 Financial Regulations bring administrative improvements to the sector, its implementation still faces structural and cultural obstacles. From the perspective of siyasah maliyah, the principles of justice, transparency and benefit have not been fully realized in village fund management practices. This research recommends strengthening the capacity of village officials and integrating siyasah maliyah values in technical regulations